Yoga for Young Adults With Noncurative Cancer: A Brief Report - Hillary Woodside MSc; S Nicole Culos-Reed PhD; Marie-Claude Grégoire MD, MSc; Robert Rutledge MD, FRCPC; Melanie R Keats PhD (SAGE Publishing, 2018)
Background The practice of yoga has been shown to improve disease- and treatment-related side effects in the noncurative cancer patient. Objective This user experience study aimed to examine the feasibility and usefulness of a DVD-based yoga program for young adult cancer patients with a noncurative diagnosis. Methods Participants were asked to partake in a 7-week DVD-based yoga program and complete measures of program use and usefulness. Results Nine patients expressed study interest and 5 consented to participate. Four completed the full study protocol. Participants reported being satisfied with the program and described that it provided an opportunity for self-care. Improvements in functional, physical, and spiritual well-being and overall quality of life were found. Barriers included competing time demands and feeling unwell. No adverse events were reported. Conclusion The program was viewed as an accessible and useful activity option; however, a desire for greater social support from relatable others was highlighted.